Juventudes rurales - Vallejo Hidalgo, Nicolás (2023)
The present article critically examines how rurality has transformed in the context of globalization, and its effects on rural youth in Ecuador, based on an intertemporal analysis of the National Survey of Employment, Unemployment and Underemployment, as well as relevant case studies that directly or indirectly focus on youth. The article aims to provide a conceptual framework for understanding rural youth that goes beyond narrow definitions based solely on age and challenges urban-centric, homogenizing, and adult-centered notions. Accordingly, drawing on theoretical perspectives on territorial development, the article identifies three major challenges that rural youth pose for rural territorial development.